Striatal Dopamine Denervation Impairs Gait Automaticity in Drug‐Naïve Parkinson's Disease Patients. Issue 6 (12th March 2020) - Hirata, Kosei; Hattori, Takaaki; Kina, Satoko; Chen, Qingmeng; Ohara, Masahiro; Yokota, Takanori
Abstract: Background: Gait automaticity, which is impaired in patients with Parkinson's disease (PD), can be quantified by gait variability analysis. Among the 3 regions of the striatum (sensorimotor, executive, and limbic), the sensorimotor region may play a crucial role in motor automaticity in healthy individuals. However, neural correlates of impaired gait automaticity are poorly investigated in PD. Objective: We aimed to examine the relationship between gait automaticity and striatal dopaminergic depletion in drug‐naïve PD patients. Methods: A total of 21 drug‐naïve PD patients and 12 healthy controls were enrolled. Gait parameters were measured via wearable inertial sensors under fast‐paced gait or cognitive dual‐task conditions, and their respective coefficient of variation (CV) and dual‐task cost were calculated. The extent of striatal dopaminergic depletion was evaluated by dopamine transporter (DAT) imaging with single‐photon emission computed tomography using N‐ω‐fluoropropyl‐2β‐carbomethoxy‐3β‐(4‐[ 123 I]iodophenyl)nortropane. Correlation between DAT uptake and gait variables was analyzed using the region‐of‐interest analysis for the 3 right or left striatal regions and voxel‐based analysis. Results: PD had higher mean bilateral CV and dual‐task cost of stride length than healthy controls. The mean bilateral CV of stride length was negatively correlated with DAT uptake in the bilateral executive regions of the striatum. Voxel‐based analysis revealed a negative correlation between the mean bilateral CV of stride length and DAT uptake in the anteromedial striatum. Conclusions: Dopaminergic denervation in the anteromedial striatum, a part of the executive region, is associated with impaired gait automaticity in drug‐naïve PD patients. This region may compensate for the posterior sensorimotor striatum, maintaining gait automaticity. © 2020 International Parkinson and Movement Disorder Society